Analisis Perhitungan Harga Pokok Produksi dengan metode Full Costing sebagai Penentu Harga Jual pada Produksi pak Kembang Cap 'KRESS’ NO' - Anam Miftakhul Huda; Dita Kurniasari; Endah Masrunik (Owner : Riset dan Jurnal Akuntansi, 2018)
Processed Industry Cap "Kress'no" is one of the business in processed opak flower industry or also called opak gambir. In determining the right price, the company must calculate the cost of goods. The goal is that the Processed Industry Cap "Kress'no" in financial processing can know the results of the measurement of basic prices within the company. Primary data used in this research using full costing method contains different value difference. The result of experiment of full costing method is Rp 5,617,00 while company method is Rp 5,566,00. From both calculations shows that the full cost calculation method is higher than the company method. Is there a difference of Rp 51.00 between full costing method and company method. Due to the company's method of Processed Industry Cap "Kress'no" has not been effective in the cost of production. Costs that have not yet been accounted for are the costs of cardboard and raffia purchases and have not yet calculated the fixed overhead cost including depreciation costs for machinery and equipment. While the full costing method. All costs incurred during production in detail.